Sistem Pendukung Keputusan Penentuan Guru Berprestasi Menggunakan Fuzzy-Analytic Hierarchy Process (F-AHP) (Studi Kasus : SMA Brawijaya Smart School) - Dewan Rizky Bahari; Edy Santoso; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Brawijaya Smart School (BSS) Senior High School Malang in producing competent and achieving students in both academic and non-academic fields requires educators / teachers with good competence in the field of education. In educational institutions, the process of determining outstanding teachers has been done relatively, school requires a certain standard in setting requirements for a teacher to get an allowance or to occupy a particular position. In addition, this assessment aims to evaluate and improve teacher's competence. In this research, a decision support system for assessment of teacher's performance using Fuzzy-Analytic Hierarchy Process (F-AHP) case study of SMA Brawijaya Smart School using six criteria there are pedagogic competence, professional competence, innovation development competence, technology utilization competence, social competence , and personality competence. The result from testing shown accuracy of system up to 82.501% with six criteria. Results of calculation, the application of Fuzzy-Analytic Hierarchy Process (F-AHP) method is expected to help the process for determining of teacher achievement in Brawijaya Smart School Malang Senior High School.